Structured populations with diffusion and Feller conditions - Agnieszka Bartłomiejczyk; Henryk Leszczyński (Mathematical Biosciences and Engineering)
We prove a weak maximum principle for structured population models with dynamic boundary conditions. We establish existence and positivity of solutions of these models and investigate the asymptotic behaviour of solutions. In particular, we analyse so called size profile.